2007
DOI: 10.1529/biophysj.106.101071
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of a Stretch-Activated Channel Inhibitor GsMTx4 with Lipid Membranes: Two Binding Modes and Effects of Lipid Structure

Abstract: Our recent molecular dynamics simulation study of hanatoxin 1 (HaTx1), a gating modifier that binds to the voltage sensor of K(+) channels, has shown that HaTx1 has the ability to interact with carbonyl oxygen atoms of both leaflets of the lipid bilayer membrane and to be located at a deep position within the membrane. Here we performed a similar study of GsMTx4, a stretch-activated channels inhibitor, belonging to the same peptide family as HaTx1. Both toxins have an ellipsoidal shape, a belt of positively ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 37 publications
6
46
0
Order By: Relevance
“…In fact, one of the main inhibitors of piezo1 and piezo2 channels is the Grammostola spatulata mechano-toxin GsTMx4 (Andolfo et al, 2013). The inhibition mechanism of this peptide is not directed against the channel, but it targets the cellular membrane, putatively penetrating the lipid bilayer and creating a transbilayer coupling (Nishizawa and Nishizawa, 2007). The abrupt change in membrane mobility induced by the presence of the link would probably affect the ability of the bilayer to transfer mechanical tension to membrane proteins and domains.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In fact, one of the main inhibitors of piezo1 and piezo2 channels is the Grammostola spatulata mechano-toxin GsTMx4 (Andolfo et al, 2013). The inhibition mechanism of this peptide is not directed against the channel, but it targets the cellular membrane, putatively penetrating the lipid bilayer and creating a transbilayer coupling (Nishizawa and Nishizawa, 2007). The abrupt change in membrane mobility induced by the presence of the link would probably affect the ability of the bilayer to transfer mechanical tension to membrane proteins and domains.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…GsMTx4 has been subjected to several computational analyses [9,10], but the interactions with membranes remain poorly understood. We expected that peptide binding would produce local deformation and local changes in membrane thickness and curvature [8,10], but these effects have not been systematically evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…When the peptide is viewed from the side of the hydrophobic protrusion, six Lys residues and one Arg residue form a ring-like structure encircling the periphery (Figure 1). Our previous simulations suggested that GsMTx4 could interact with the lipid bilayer through a shallow (interfacial) binding mode and a deeper mode [9] wherein some Lys residues interacted with lipid head groups of the inner monolayer while the remaining Lys interacted with head groups of the outer monolayer. At low concentrations GsMTx4 inhibits bacterial channels MscS and MscL, but at higher concentrations there may be potentiation which might reflect a concentration-dependent transition from shallow to deep binding mode [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the same way an interaction of CsTx-1 with the ion channel surrounding lipid layer is also thinkable. Such a case could be shown for GsMTx4, a specific inhibitor for pro-and eukaryotic stretch-activated mechanosensitive channels acting via bilayer tension (33,34). The neurotoxic activity of the ICK structure of CsTx-1 is then further synergistically assisted by the pore-forming activity of the peptide C-terminal ␣-helical part.…”
Section: Discussionmentioning
confidence: 96%